O conceito de tolerância em John Locke: a tolerância universal e os seus limites - Diniz, Márcio Victor de Sena (2011)
John Locke (1632-1704) is an important philosopher of Modern Age. His most important researches focus on the epistemology, theology, ethics and political philosophy. Among the themes investigated by Locke, it is present the problem of religious tolerance, on which the philosopher devoted more than four decades, between 1660 and 1704. During this period, we can characterize at least two different positions adopted by Locke on the relationship between the political and religious fields. The first position corresponds to the earliest writings about the Lockean tolerance: Two Tracts on Government (1660-62). In this period, Locke defends that the civil magistrate is entitled to impose laws on some religious aspects, that is, about the indifferent things". The strongest allegation of the philosopher is that only through religious uniformity in terms of "indifferent things", is that the magistrate could ensure order within the civil community, preventing the peace from been disturbed by religious disputes. The second Lockean position corresponds mainly to Epistola de tolerantia (1689). In this time, Locke changes his argument and begins to defend religious tolerance, basing exactly on the separation of the State and Church and setting different functions for each of these institutions, as well as their own powers to perform their proper functions. The objective of this study is to investigate the different concepts of tolerance in the three works presented above. We will defend two hypotheses about the Lockean tolerance. 1. First, we will support that, despite of the change in Locke's position on the relationship between the State and Church, the philosopher remains an element unchanged over his writings on tolerance, namely, his "theological conception", and we will claim that this "theological conception" is essential to understand the Lockean concept of tolerance. 2. We will defend that the concept of tolerance presented in Epistola of 1689 can elucidate the political and religious problems encountered in the context of the Protestant Reform and religious wars occurred in Europe during the sixteenth and seventeenth centuries.